Improving the Quality of Education in Public Primary School - Masuri, Masuri; Fitria, Happy; Mulyadi, Mulyadi (Yayasan Sembilan Pemuda Indonesia, 2021)
This study described the quality of learning in Public Primary Schools 22 Banyuasin III. The qualitative method was used in the study. Informants were headmaster and teachers. Data were collected using interviews. The results showed that the management of grade teachers in the implementation of the teaching process relevant with the era of the industrial revolution 4.0. The obstacles were lack of visual aids.